2005
DOI: 10.1126/science.1120615
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Binding Domains in Y-Family Polymerases Regulate Translesion Synthesis

Abstract: Translesion synthesis (TLS) is the major pathway by which mammalian cells replicate across DNA lesions. Upon DNA damage, ubiquitination of proliferating cell nuclear antigen (PCNA) induces bypass of the lesion by directing the replication machinery into the TLS pathway. Yet, how this modification is recognized and interpreted in the cell remains unclear. Here we describe the identification of two ubiquitin (Ub)-binding domains (UBM and UBZ), which are evolutionarily conserved in all Y-family TLS polymerases (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
896
4
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 641 publications
(935 citation statements)
references
References 17 publications
25
896
4
6
Order By: Relevance
“…Second, the high levels of monoubiquitinated PCNA (due to the loss of USP1) may result in the recruitment and competition of other error-prone TLS polymerases (such as Rev3-Rev7, Rev1, polκ and polι) with polη for undamaged and damaged DNA templates. A recent study has identified two ubiquitin-binding domains (UBM and UBZ) that are evolutionarily conserved in all Y-family TLS polymerases (Rev1, polκ, polι and polη) 12 . These domains are required by polη and polι (and possibly other Y-family TLS polymerases) for interaction with monoubiquitinated PCNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the high levels of monoubiquitinated PCNA (due to the loss of USP1) may result in the recruitment and competition of other error-prone TLS polymerases (such as Rev3-Rev7, Rev1, polκ and polι) with polη for undamaged and damaged DNA templates. A recent study has identified two ubiquitin-binding domains (UBM and UBZ) that are evolutionarily conserved in all Y-family TLS polymerases (Rev1, polκ, polι and polη) 12 . These domains are required by polη and polι (and possibly other Y-family TLS polymerases) for interaction with monoubiquitinated PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a model has emerged in which polη binds to monoubiquitinated PCNA and ensures accurate (error-free) replicative bypass of UV lesions. However, other (error-prone) TLS polymerases (such as polι and Rev1) have recently been shown to rely on monoubiquitinated PCNA for their function 12,13 . How cells limit PCNA monoubiquitination and the unwanted deployment of polη and/or other error-prone TLS polymerases in the absence or presence of extrinsic DNA damage during the synthesis of DNA in S phase is not known.…”
mentioning
confidence: 99%
“…PCNA is monoubiquinated at lysine residue 164 in human cells after UV-irradiation, and it has been proposed that this modification may mediate the exchange between replicative and TLS polymerases when the replication fork arrests at a lesion 93 . Accordingly, TLS polymerases bind to monoubiquitinated PCNA through two types of motif: a PCNA interacting peptide (PIP box) that binds directly to PCNA 94 and an ubiquitin-binding motif that is required for their bypass function 95 . The role of PCNA in SHM was analysed using mice bearing a PCNA mutation (Lys164Arg) that is known to inhibit its monoubiquitination and therefore its interaction with TLS polymerases.…”
Section: Polη the Study Of Patients Affected By The Xeroderma Pigmenmentioning
confidence: 99%
“…Mono-ubiquitination of PCNA increased its affinity for polη, so that their interaction could be detected in cell extracts [25,26]. It was shown subsequently that not only polη, but also polι, Rev1 and polκ have novel ubiquitinbinding domains (UBDs), and that at least in the case of polη and polι (and likely for polκ and Rev1 also), the polymerases were able to bind to ubiquitin [30]. Thus, the combination of binding to ubiquitinated PCNA via both the PIP motif and the UBDs strengthens the interactions between the polymerases and PCNA, facilitating their recruitment to the stalled fork and facilitating the polymerase switch.…”
Section: Recruitment To the Replication Forkmentioning
confidence: 99%